Pengaruh Positive Emotion, Time Availability, dan Money Availability terhadap Impulsive Buying Behavior Konsumen Mahasiswa pada Department Store di Kota Yogyakarta - Ardiyanto, Faizal (AKMENIKA, 2017)
This research was conducted to examine the influence of positive emotion, time availability, and money availabilty toward impulsive buying behavior both partially and simultaneously. The respondent of this research are university students who have experienced unplanned buying in several department stores at Yogyakarta City. Purposive sampling method was utilized then 102 respondents were chosen. The results indicate that positive emotion, time availability, and money avaiability positively and significantly influence impulsive buying behavior. The three independent variables as stated above, simultaneously influence impulsive buying behavior also. Finally, as the managerial implication stated, it can be concluded that understanding consumers condition related with unplanned buying is important topics in recent years, especially in department store.